2019
DOI: 10.3390/admsci9020032
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of Small and Medium-Sized Enterprises in Saudi Arabia: Insights from Sustainability Perspective

Abstract: : The aim of this study is to explore the critical success factors (CSFs) of small and medium-sized enterprises (SMEs) in Saudi Arabia. A questionnaire was developed using 28 factors/indicators identified from the previous researches. From 500 respondents, a total of 347 questionnaires were returned. By conducting exploratory factors analysis, these indicators were categorized into six factors, namely: Individual factors, business characteristics, management factors, business support, capital availability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 30 publications
1
61
0
2
Order By: Relevance
“…On the other hand, all the values of the average variance extracted (AVE) were greater than 0.50 (Al-Ayed, 2019; Almohaimmeed, 2017; Al-Tit, 2016), which indicated that validity was assured. Reliability was also supported; that is, the composite reliability (CR) values and Cronbach's alpha coefficients (α) were greater than 0.7 (Al-Tit et al, 2019;Sweis et al, 2013).…”
Section: Exploratory Factor Analysismentioning
confidence: 97%
“…On the other hand, all the values of the average variance extracted (AVE) were greater than 0.50 (Al-Ayed, 2019; Almohaimmeed, 2017; Al-Tit, 2016), which indicated that validity was assured. Reliability was also supported; that is, the composite reliability (CR) values and Cronbach's alpha coefficients (α) were greater than 0.7 (Al-Tit et al, 2019;Sweis et al, 2013).…”
Section: Exploratory Factor Analysismentioning
confidence: 97%
“…This is despite the fact that SMEs account for about 95 percent of businesses globally, and in most countries they contribute more than half of the employment and GDP (Organization for Economic Cooperation and Development [OECD], 2017;United Nations, 2019;World Bank, 2019). The neglect has been linked to their size, as it is assumed that because of their size their impact on the business environment is minimal (Panwar et al, 2017;Edgell, 2018;Al-Tit et al, 2019). Although individually their impact may be minimal, their collective CSR impact is huge (OECD, 2017;Edgell, 2018;Takalendze & Mohammed, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Al Tit [27] categorized most important indicators for success of SMEs, by introducing business performance indicators, business characteristics, and business environment. Formisano [28] studies sustainability from a business perspective, identifying financial performance as relevant for comparison between businesses.…”
Section: Key Indicators Of Business Performance In Smesmentioning
confidence: 99%